Profitabilitas Sebagai Mediasi Pertumbuhan Penjualan dan Struktur Modal terhadap Nilai Perusahaan - Bayu Ajie Santoso; Anindhyta Budiarti (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
This research aimed to analyze and find out the effect of sales growth and capital structure on the firm value, with profitability as moderating variable. In line with, there were 11 Property and Real estate companies which were listed on Indonesia Stock Exchange 2014-2018 as samples. In addition, the data analysis technique used path analysis with Smart PLS 3.0. The research result concluded Sales Growth (SG) and Debt to Equity Ratio (DER) had positive and significant effect on Return On Equity (ROE). Meanwhile, Sales Growth (SG) and Return On Equity (ROE) had negaitve and insignificant effect as well as Debt to Equity Ratio (DER) had negaitve and significant effect on the Price to Book Value (PBV). In short, profitability did not mediate the effect of Sales Growth (SG) and Debt to Equity Ratio (DER) on Price to Book Value (PBV).